Experiences perceptions and understanding of mothers of children living with albinism in Malawi: a qualitative descriptive study - Likumbo, Naomi (Division of Nursing and Midwifery, 2020)
Background: Albinism affects approximately 1 in 17,000 individuals globally with the highest prevalence in SubSaharan Africa with an estimation of 1 in 2000 - 5000 live births and 1 in 2000 live births in Malawi. The total number of people living with albinism in Malawi is estimated to be 7000 - 10,000 of the total population. Albinism is a stigmatised condition particularly in Africa and children are particularly vulnerable. Purpose of the study: to explore and describe the experiences, perceptions and understanding of mothers who have children living with albinism in Malawi. Study design: Qualitative descriptive study. Data collection Methods: The study, conducted between June and July 2018 in Malawi, included voluntary participation of ten mothers 18 years and older who had children with albinism. Purposive sampling was used to select participants who met the inclusion criteria to answer the research question and achieve the purpose of the study. Semi structured interviews were conducted in the participants’ preferred language Chichewa. Interviews were audio recorded and transcribed. Data translation of the questionnaire from English to Chichewa was done by three different translators from Malawi using forward and backward translation. The same process was followed for translation of the data from the interviews. Data analysis: Thematic analysis guided the process of data analysis. Trustworthiness of the data analysis process was maintained. To ensure transparency in reporting the study and to allow replication, reporting guidelines from the equator Network were used to evaluate the quality of the study. The quality of semistructured interviews was evaluated by using the Consolidated Criteria for Reporting Qualitative Studies (COREQ), a 32-item checklist. The Standards for Reporting Qualitative Research (SRQR) were used to evaluate the quality of the completed study. Findings: Four themes emerged from the data: 1) stigmatisation, discrimination and harm, 2) Mothers’ impression of a child with albinism, 3) Mothers’ awareness of albinism and 4) Psychosocial effects of albinism. Conclusion: A description of the experiences and perceptions of mothers of children living with albinism in Malawi and their understanding of the condition has revealed that these children are stigmatised and unsafe in their communities and that these mothers experienced this acutely even though they were overwhelmingly positive about accepting and loving their children and attempted to protect them from harm whatever the cost. Being the first such reported Malawian study it has filled a gap in the existing knowledge in this field and provides a foundation for further research specific to people living with albinism in Malawi